Detection of Bacillus cereus in formula milk and ultra high temperature (UHT) treated milk products - Bilung, Lesley Maurice; S. R., Ernie; Apun, Kasing; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Ultra high temperature (UHT) treated milk products and formula milk are known to be frequently contaminated with Bacillus cereus. Presence of B. cereus in these milk products is of particular concern considering the majority of consumers are infants and children. Possible sources of contamination are contaminated raw milk, cross-contamination during processing, under-processing and mishandling of milk products. This study was conducted to detect the presence of B. cereus in both formula milk (n=12) and UHT milk (n=20) sold in selected retail markets. The approach consisted of enumerating by MPN/g followed by PCR assay aimed at detecting gyrB gene in B. cereus, that encode for the subunit B protein of DNA gyrase (topoisomerase type II). Contamination level of B. cereus in both types of samples examined ranged from < 3 to > 1100 MPN/g. The contamination level of B. cereus was found to be highest in full cream UHT milk (> 1100 MPN/g) and formula milk (> 1100 MPN/g). The PCR analysis showed that 41.7% (5/12) formula milk and 30% (6/20) UHT milk samples were detected with B. cereus, respectively. This is the first report of such study demonstrating the presence of B. cereus in formula milk from Malaysia. Therefore, constant surveillance of these milk products would reduce the potential risk of B. cereus-linked outbreaks.